An insulin-to-insulin regulatory network orchestrates phenotypic specificity in development and physiology. - Diana Andrea Fernandes de Abreu; Antonio Caballero; Pascal Fardel; Nicholas Stroustrup; Zhunan Chen; Kyunghwa Lee; William D Keyes; Zachary M Nash; Isaac F López-Moyado; Federico Vaggi; Astrid Cornils; Martin Regenass; et al. (PLoS Genetics)
Insulin-like peptides (ILPs) play highly conserved roles in development and physiology. Most animal genomes encode multiple ILPs. Here we identify mechanisms for how the forty Caenorhabditis elegans ILPs coordinate diverse processes, including development, reproduction, longevity and several specific stress responses. Our systematic studies identify an ILP-based combinatorial code for these phenotypes characterized by substantial functional specificity and diversity rather than global redundancy. Notably, we show that ILPs regulate each other transcriptionally, uncovering an ILP-to-ILP regulatory network that underlies the combinatorial phenotypic coding by the ILP family. Extensive analyses of genetic interactions among ILPs reveal how their signals are integrated. A combined analysis of these functional and regulatory ILP interactions identifies local genetic circuits that act in parallel and interact by crosstalk, feedback and compensation. This organization provides emergent mechanisms for phenotypic specificity and graded regulation for the combinatorial phenotypic coding we observe. Our findings also provide insights into how large hormonal networks regulate diverse traits.